Four-hour cough frequency monitoring in chronic cough. - Lee, K; Savani, A; Matos, S; Evans, D; Pavord, I; Birring, S (2012)
BACKGROUND: The recent development of automated cough monitors has enabled objective assessment of cough frequency. A study was undertaken to determine whether short-duration recordings( < 6 h) accurately reflect 24-h cough frequency and to investigate their responsiveness. METHODS: One hundred adults with chronic cough underwent 24-h cough frequency monitoring with the Leicester Cough Monitor and completed cough visual analog scales (VASs) and the Leicester Cough Questionnaire (LCQ). Cough recordings were analyzed using customized software to derive cough frequencies from 1 to 6 h and 24-h recordings. Responsiveness was assessed with repeat assessments following therapeutic trials. RESULTS: The median (interquartile range) 24-h cough frequency was 11.5 (5.8-26.6) coughs/h. Four hours was considered the shortest recording duration that represented 24-h cough frequency( ρ= 0.9, P ≤ .001). Median 4-h cough frequency was 16.6 (7.3-36.8) coughs/h. Both 4-h and 24-h cough frequency correlated moderately with cough VAS ( ρ= 0.49, P ≤ .01 and ρ= 0.44, P ≤ .01)and LCQ ( ρ = - 0.48, P ≤ .01; ρ = - 0.50, P ≤ .01). Four-hour cough frequency was responsive to improvements in cough severity following trials of therapy. CONCLUSIONS: Four-hour cough frequency correlates highly with 24-h cough frequency recordings and relates equally well with subjective measures in chronic cough. Short-duration cough monitoring could be a practical tool to validate the presence of cough and assess response to trials of therapy in the clinic setting.